EFEKTIVITAS PENYELESAIAN MASALAH VERIFIKASI TERKAIT LANDREFORM OLEH OMBUDSMAN REPUBLIK INDONESIA PERWAKILAN PROVINSI LAMPUNG (Studi pada Laporan Mayarakat Register Nomor: 0009/LM/I/2021/BDL) - Handayani, Yusni; Farida, Ida (JURNAL SOSIAL DAN HUMANIS SAINS, 2022)
ABSTRACT The level of effectiveness of public services can be reviewed when the community obtains services with procedures in accordance with applicable regulations. However, in practice there are violations in public services, so an external supervisory agency is needed, one of which is the Ombudsman of Indonesia. At the Ombudsman of the Republic of Indonesia, the Representative of the Province of Lampung received a report, because the Reporting Party did not obtain their rights in public services at the National Land Agency (BPN). The out come of this analysis is to spell out the effective of solving verification problems related to land reform by the Ombudsman of the Republic of Indonesia, the Representative of the Province of Lampung, as well as the inhibiting and supporting factors. This is especially true for public reports with register number 0009/LM/I/2021/BDL. This research method is qualitative. The information analysis method upon the analysis uses discussion, observation and documentation method. The outcome reveal that the completion of the verification problem related to land reform by the Ombudsman of Lampung, resespecially reports with register number 0009/LM/I/2021/BDL went well and effectively. This is because the four indicators used to assess the effectiveness of solving verification problems related to lan reform by the Ombudsman of Lampung in a public report with register number 0009/LM/I/2021/BDL have been completed and closed with the results of the Reported Party carrying out its obligations to the Reported Party. . reported. There are only a few inhibiting factors, namely the lack of Human Resources (HR) in carrying out their duties at the Ombudsman of the Republic of Indonesia Representative of the Province of Lampung.